2013
DOI: 10.2807/1560-7917.es2013.18.47.20637
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B prevalence in Denmark – an estimate based on nationwide registers and a national screening programme, as on 31 December 2007

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…These groups also have difficulties accessing the existing health system and may have poor knowledge of the diseases and risk factors[12]. …”
Section: Introductionmentioning
confidence: 99%
“…These groups also have difficulties accessing the existing health system and may have poor knowledge of the diseases and risk factors[12]. …”
Section: Introductionmentioning
confidence: 99%
“…The male to female ratio in the case of inflammatory conditions turned out to be lower (0.6 to 2.3) when compared to cases of acute hepatitis B (0.5 to 5.2) (24). However, according to the data provided by the Danish National Board of Health, the estimated incidence rate of chronic hepatitis B in the population under 16 years of age registered prior to 31 December 2007 (including undiagnosed patients) was 0.24, and the rate was a little higher among men (25). The results of studies from Iran confirm the gender differences revealed earlier in the incidence rates of chronic carrier states of the HBs antigen to the disadvantage of men (26).…”
Section: Discussionmentioning
confidence: 99%
“…The rise in the number of chronic hepatitis B cases may be associated with the increased number of tests performed, but also with a growing migration of hepatitis cases from the countries with high hepatitis B incidence rates, which has been reported in many European countries and the USA (23, 25, 33, 34, 36, 37). …”
Section: Discussionmentioning
confidence: 99%
“…Even in countries where all citizens have unique identification codes -for example Denmark where markrecapture has been used to estimate the prevalence of hepatitis (Christensen et al, 2012;Hansen et al, 2014) -issues relating to data protection legislation and client or patient confidentiality are becoming more and more prominent. While it is possible to construct unique numeric codes to anonymise or "pseudonymise" personal data, since these are based on personal data the data protection concerns still remain (along with all the attendant data security issues such as safe storage and transfer).…”
Section: Discussionmentioning
confidence: 99%